The Correlation between EFL Students' Use of ICT Level and Their Autonomous Learning Level - Devon Evita; Siti Muniroh; Nunung Suryati (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Information and Communication Technology is a basic need for life nowadays, including education. Many people believe that ICT can promote students’ autonomous learning. Thus, this study was conducted to find whether ICT usage and autonomous learning are correlated, and to compare the attitudes between Indonesian and Moroccan EFL students. This study used quantitative correlational design. The participants were 97 English Department students of Universitas Negeri Malang. The instrument was a questionnaire with 28 items: 14 questions for ICT usage and 14 (items/questions) for autonomous learning. The data were analyzed using Pearson Product Moment Correlation Coefficient in SPSS 25 application. The findings revealed that ICT usage and autonomous learning are correlated. The other findings are Indonesians EFL students like to have discussions with peers, while Moroccans like to look for information themselves. Moreover, Indonesians have very high self-awareness and low self-confidence, meanwhile Moroccans have very high self-effort and autonomy in planning. This study brings significance to teaching practice to inform how far ICT usage contributes to autonomous learning, especially in the Covid-19 outbreak. The researcher recommended that future researchers widen the participants’ total and use the other variables outside this study’s variables since ICT usage only contributes 22.1% to autonomous learning. Keywords: ICT use; autonomous learning; EFL students Abstrak: Teknologi Informasi dan Komunikasi merupakan kebutuhan dasar di kehidupan jaman sekarang, termasuk pendidikan. Banyak orang percaya bahwa TIK dapat memicu otonomi belajar siswa. Maka dari itu, penelitian ini diadakan untuk menemukan korelasi antara penggunaan TIK dan otonomi belajar siswa serta membandingkan sikap mahasiswa Bahasa Inggris sebagai Bahasa Asing Indonesia dengan Maroko. Penelitian ini menggunakan desain korelasi kuantitatif. Pesertanya adalah 97 mahasiswa jurusan Sastra Inggris Universitas Negeri Malang. Instrumennya menggunakan kuesioner yang terdiri dari 28 item, 14 untuk penggunaan TIK dan 14 untuk otonomi belajar. Data dianalisis menggunakan Pearson Product Moment Correlation Coefficient pada aplikasi SPSS 25. Hasilnya, penggunaan TIK dan otonomi belajar saling berhubungan. Temuan lainnya yaitu mahasiswa Indonesia suka berkomunikasi dengan teman, sedangkan mahasiswa Maroko suka mencari informasi sendiri. Selain itu, mahasiswa Indonesia memiliki kesadaran diri yang sangat tinggi dan kepercayaan diri yang rendah, sedangkan mahasiswa Maroko memiliki kemandirian dan otonomi perencanaan yang sangat tinggi. Penelitian ini membawa signifikansi pada praktik mengajar karena menginformasikan sejauh mana penggunaan TIK berkontribusi terhadap belajar mandiri, terutama di masa wabah Covid-19. Peneliti merekomendasikan peneliti selanjutnya untuk memperluas total peserta dan menggunakan variabel lain di luar variabel penelitian ini karena penggunaan TIK hanya berkontribusi 22,1% terhadap belajar mandiri. Kata kunci: penggunaan TIK; belajar mandiri; siswa bahasa Inggris sebagai bahasa asing